Mantenimiento predictivo aplicando técnicas: visuales, termográficas, efecto corona y ultrasonido acústico para detectar anomalías y prever interrupciones de energía eléctrica, no programadas, de las líneas de subtransmisión en el Ecuador. - Cruz Loya, Edwin Vinicio (2021)
The Subtransmission power lines are routes that connect distribution substations. In Ecuador there are several kilometers of these routes, operated by 20 electricity companies and the vast majority are radial systems, which due to a failure can disable distribution substations, which can leave several users without service, affecting power supply. distributor in the service quality indexes. It is important to mention that most of these lines are older than 25 years of construction, which makes them more susceptible to failure of mechanical and electrical elements, which are prone to corrosion and degradation; due to climatic factors, end of useful life, mechanical and electrical stresses, affectation by flora and fauna, etc. A failure can leave a large number of customers without electricity service, causing them great economic losses that will never be recovered and preventing commercial and industrial development, at the same time, penalties and fines are generated for distribution companies, existing both for the customer and for the supplier irrecoverable losses.- Therefore, due to the fact that it is very expensive to make ringed systems, and at the moment there is no solution to the case; And since there are no rules and procedures for predictive maintenance in electrical sub-transmission systems, predictive maintenance processes that support the maintainability of sub-transmission lines will be analyzed with visual inspection techniques, infrared thermography, corona effect and acoustic ultrasound, with drones. and on foot, to find possible anomalies and avoid unscheduled disconnections of the subtransmission lines in Ecuador.